Can targeted industrial policy drive low-carbon transformation? evidence from China’s Five-Year Plans - Song, Li; Yuan, Jiali; Li, Ting; Zhang, Jianzhong (Frontiers in Environmental Science, 2025)
Facing escalating climate challenges, the Chinese government has highlighted the importance of targeted industrial policy for driving low-carbon transformation within its Five-Year Plans, whose effectiveness warrants evaluation. This paper employs a fixed-effects model across provinces, industries, and years, adopting data from 36 sectors across 30 Chinese provinces from 1997 to 2019, to assess the impact of the targeted industrial policy on low-carbon transformation. We reveal that industries receiving targeted support exhibit a 9.2% higher low-carbon transformation index than those without. The effects of industrial policy on low-carbon transformation are more pronounced in the context of local government policy, recent Five-Year Plans, sectors with moderate to low technological complexity, and high-emission sectors. Mechanism analysis shows that industrial policy facilitates low-carbon transformation by structural effects and technological effects. These insights offer a foundation for refining industrial policy design and execution to achieve carbon neutrality goals and foster sustainable growth.